In vitro activities of the spectinomycin analog U-63366 and four quinolone derivatives against Neisseria gonorrhoeae. - Peeters, M (1984)
The in vitro activities of the new spectinomycin analog U-63366 and four new quinolone derivatives, rosoxacin, norfloxacin, ofloxacin, and ciprofloxacin, were compared with those of penicillin, tetracycline, thiamphenicol, cefotaxime, ceftriaxone, and spectinomycin against 222 beta-lactamase-negative and 25 beta-lactamase-positive Neisseria gonorrhoeae strains. U-63366 was more active than spectinomycin, inhibiting 90% of the strains at a concentration of 2 mg/liter. Among the quinolone derivatives, ciprofloxacin was the most active compound in vitro (90% MIC, 0.002 mg/liter), followed by ofloxacin (90% MIC, 0.008 mg/liter), norfloxacin (90% MIC, 0.015 mg/liter), and rosoxacin (90% MIC, 0.03 mg/liter).